Erector Spinae Plane Block VS. Thoracic Paravertebral Block for Video Assisted Thoracoscopic Surgery (Vats): A Comparative Analysis of Regional Anesthesia Techniques on Current Literature - Christan Chaputtra Maharibea; I Gusti Ngurah Mahaalit Aribawaa (Journal of Social Research, 2026)
Video-assisted thoracoscopic surgery (VATS) has become a widely adopted minimally invasive thoracic procedure because it reduces surgical trauma, postoperative complications, and hospital length of stay compared with conventional thoracotomy. However, postoperative pain after VATS remains a significant clinical challenge that may impair respiratory function, delay mobilization, and prolong recovery. Regional anesthesia techniques such as erector spinae plane block (ESPB) and thoracic paravertebral block (TPVB) are increasingly incorporated into enhanced recovery after surgery (ERAS) protocols, although their comparative effectiveness remains under debate. This study aimed to compare the analgesic efficacy, perioperative outcomes, and safety profiles of ESPB and TPVB in patients undergoing VATS. This research employed a narrative review design by synthesizing evidence from randomized controlled trials, comparative studies, and meta-analyses published between 2021 and 2026. Data were collected from PubMed, Scopus, and Web of Science databases using a structured literature search strategy. The findings demonstrated that both ESPB and TPVB provide comparable postoperative analgesia, opioid consumption, respiratory recovery, and length of hospital stay within the first 24–48 hours after surgery. TPVB showed slightly superior early pain control, whereas ESPB offered greater procedural simplicity and a lower risk of pleura-related complications. In conclusion, both techniques are effective regional anesthesia options for VATS, and their selection should be individualized based on clinical priorities, surgical complexity, and patient safety considerations.